2017
DOI: 10.1186/s12966-017-0509-8
|View full text |Cite
|
Sign up to set email alerts
|

The association between social support and physical activity in older adults: a systematic review

Abstract: BackgroundThe promotion of active and healthy ageing is becoming increasingly important as the population ages. Physical activity (PA) significantly reduces all-cause mortality and contributes to the prevention of many chronic illnesses. However, the proportion of people globally who are active enough to gain these health benefits is low and decreases with age. Social support (SS) is a social determinant of health that may improve PA in older adults, but the association has not been systematically reviewed.Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
336
2
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 596 publications
(369 citation statements)
references
References 97 publications
(223 reference statements)
22
336
2
9
Order By: Relevance
“…Similar findings were reported by Rai et al (2019) and Jones, Wen, Herring, and Evenson (2016). At the interpersonal level, social support has been positively associated with physical activity (Bauman et al, 2012;Smith, Banting, Eime, O'Sullivan, & van Uffelen, 2017;Thornton et al, 2017). Environmental factors-which relate to institutional, community, and policy levels of influence-have also been associated with physical activity, such as a positive association between physical activity and proximity to recreational facilities (Bauman et al, 2012;Thornton et al, 2017) and transportation environment safety/walkability (Bauman et al, 2012;O'Donoghue et al, 2016).…”
Section: Ecological Factors Associated With Physical Activitysupporting
confidence: 73%
“…Similar findings were reported by Rai et al (2019) and Jones, Wen, Herring, and Evenson (2016). At the interpersonal level, social support has been positively associated with physical activity (Bauman et al, 2012;Smith, Banting, Eime, O'Sullivan, & van Uffelen, 2017;Thornton et al, 2017). Environmental factors-which relate to institutional, community, and policy levels of influence-have also been associated with physical activity, such as a positive association between physical activity and proximity to recreational facilities (Bauman et al, 2012;Thornton et al, 2017) and transportation environment safety/walkability (Bauman et al, 2012;O'Donoghue et al, 2016).…”
Section: Ecological Factors Associated With Physical Activitysupporting
confidence: 73%
“…In older adults, a higher SS is associated with decreased rates of both morbidity and mortality [28], improved physiological health parameters [29], and a higher QOL [30]. Furthermore, several studies have reported a positive relationship between social ties and PA in the elderly [31, 32]. …”
Section: Conceptualization Of Central Terms and Evidence About Associmentioning
confidence: 99%
“…Based on research examining correlates of MVPA, perceived social support was expected to be positively associated with LPA and higher unsupportive partner response to cancer was expected to be negatively associated with LPA. Instead, results revealed no significant association of perceived social support and LPA.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, among those not engaging in any MVPA, greater unsupportive partner behaviors increased odds of engaging in LPA. Although research has demonstrated consistent associations between social support and physical activity among aging adults and cancer survivors, less research has examined the relative influence of undermining behaviors, or the support source's proximity to the cancer survivor. It may be that the influence of social support on LPA varies based on a variety of factors such as support type (ie, emotional vs practical), the source of support (eg, partner, family member, friend, support group), the proximity/dose of support (eg, living with support source vs geographically remote), and the presence of undermining behaviors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation